2010
DOI: 10.1007/s10529-010-0343-4
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid improves podophyllotoxin production in cell cultures of Linum album by increasing the expression of genes related with its biosynthesis

Abstract: Treatment of Linum album cell cultures with 10 μM salicylic acid (SA) for 3 days improved podophyllotoxin (PTOX) production up to 333 μg/g dry weight (DW): over three times that of the control cultures. qPCR analyses showed that in SA-treated cells, the expression of the genes coding for phenylalanine ammonia-lyase (PAL), cinnamoyl-CoA reductase (CCR) and cinnamyl-alcohol dehydrogenase (CAD), all involved in the first steps of PTOX biosynthesis, also increased reaching a peak 8-12 h after the treatment. Expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 14 publications
(15 reference statements)
2
32
0
Order By: Relevance
“…Meanwhile, many studies used SA to improve the biosynthesis of important metabolic compounds in cell or hairy-root cultures of different plant species, e.g. jaceosidin and siringin from Saussurea medusa (11), flavonolignans and lipoxygenase from Silybum marianum (12), phenolic metabolism in Matricaria chamomilla (13), metabolic changes of Catharanthus roseus cell cultures (14), podophyllotoxin from Linum album (15), and taxol from Taxus baccata (16). In a previous report, we showed a stimulatory effect of SA on the biosynthesis of asiaticoside in centella cells (17).…”
Section: Results and Conclusion: The Cell Fresh (Dry) Biomass Increamentioning
confidence: 99%
“…Meanwhile, many studies used SA to improve the biosynthesis of important metabolic compounds in cell or hairy-root cultures of different plant species, e.g. jaceosidin and siringin from Saussurea medusa (11), flavonolignans and lipoxygenase from Silybum marianum (12), phenolic metabolism in Matricaria chamomilla (13), metabolic changes of Catharanthus roseus cell cultures (14), podophyllotoxin from Linum album (15), and taxol from Taxus baccata (16). In a previous report, we showed a stimulatory effect of SA on the biosynthesis of asiaticoside in centella cells (17).…”
Section: Results and Conclusion: The Cell Fresh (Dry) Biomass Increamentioning
confidence: 99%
“…The inefficiency of SA in promoting valtrate production in adventitious roots of Valeriana amurensis has also been reported [42]. However, several studies have shown the effectiveness of SA in improving target metabolites in the plant cells [35,43]. SA and Jasmonic acid (JA)/MJ are messengers in the signal transduction chains involved in different pathways of biosynthesis and in activation of secondary metabolites and enzymes that participate in the plant stress response [44]; and exogenous application of MJ and SA may also induce the expression of many defense genes in plants [45].…”
Section: êmentioning
confidence: 95%
“…Cell suspension cultures of L. album were prepared from leaf explants-derived calliin 50 mL of Murashige and Skoog (1962) medium supplemented with 30 g/L sucrose, 2 mg/L naphthalene acetic acid, and 0.4 mg/L kinetin (Yousefzadi, Sharifi, Behmanesh, Moyano, & Palazon 2010). All suspension cultures were incubated on a gyratory shaker at 120 rpm in darkness at 25°C and subcultured every week.…”
Section: Cell Suspension Culturesmentioning
confidence: 99%
“…Lignans were extracted from cells by sonication in methanol/water, as previously described (Yousefzadi, Sharifi, Behmanesh, Moyano, & Palazon 2010). The extract was dissolved in methanol again, and filtered through a Millex-LH filter with 0.45 µm pore size (Millipore, Bedford, MA, USA).…”
Section: Determination Of Lignans By High Pressure Liquid Chromatogramentioning
confidence: 99%
See 1 more Smart Citation